Correlation of whole-bone marrow dual-time-point (18)F-FDG, as measured by a CT-based method of PET/CT quantification, with response to treatment in newly diagnosed multiple myeloma patients - Zirakchian Zadeh, Mahdi (Am J Nucl Med Mol Imaging, 2020)
The practical application of dual-time-point-imaging (DTPI) technique still remains controversial. One of the issues is that current parameters of DTPI quantification suffer from some deficiencies, mainly limited sampling of the diseased sites by confining measurements to specific locations. We aimed to examine the correlation between the percent change from early to delayed scans in whole-bone marrow (WBM) (18)F-FDG uptake, as measured by a CT-based method of PET/CT quantification, and response to treatment in multiple myeloma (MM) patients. Pre-treatment (18)F-FDG-PET/CT scans of 36 newly diagnosed MM patients were collected in a prospective study at 1 h and 3 h post tracer injection (NCT02187731). A threshold algorithm based on bone Hounsfield units on CT was applied to segment and quantify WBM (18)F-FDG uptake. Patients were separated into two treatment groups: high-dose therapy with autologous stem cell transplant (HDT) and non-high dose therapy (non-HDT). The International Response Criteria for MM patients was used to determine each patient’s response to treatment. In the HDT group, WBM (18)F-FDG uptake increased significantly in patients that had a poor response to treatment, from a median of 1.31 (IQR: 1.13-1.64) at 1 h to a median of 1.85 (1.45-2.10) at 3 h. The median percent change was 37.77% (IQR: 23.47-46.4), with a range of 6.10-50.73 (P = 0.003). However, no significant change in uptake was observed in patients with a complete response (P = 0.24). The same trend was observed for the non-HDT group. WBM uptake of (18)F-FDG assessed with dual-time-point imaging may have a role in predicting treatment response in MM.